Antigens from the parasitic nematode Trichuris suis induce metabolic reprogramming and trained immunity to constrain inflammatory responses in macrophages. (August 2022) - Zakeri, Amin; Everts, Bart; Williams, Andrew R.; Nejsum, Peter
Abstract: Regulation of macrophage (Mɸ) function can maintain tissue homeostasis and control inflammation. Parasitic worms (helminths) are potent modulators of host immune and inflammatory responses. They have evolved various strategies to promote immunosuppression, including redirecting phagocytic cells toward a regulatory phenotype. Although soluble products from the whipworm Trichuris suis (TSPs) have shown significant effects on Mɸ function, the mechanisms underlying these modulatory effects are still not well understood. In this study, we find that TSPs suppressed inflammatory cytokines (TNF and IL-6) in Mɸs stimulated with a broad panel of TLR agonists, whilst inducing IL-10. Moreover, M1 markers such as MHCII, CD86, iNOS, and TNF were downregulated in TSP-treated Mɸs, without polarizing them towards an M2-like phenotype. We showed that TSPs could establish a suppressed activation state of Mɸs lasting at least for 72 h, indicating an anti-inflammatory innate training. Moreover, we found that TSPs, via repression of intracellular TNF generation, decreased its secretion rather than interfering with the release of surface-bound TNF. Metabolic analysis showed that TSPs promote oxidative phosphorylation (OXPHOS) without affecting glycolytic rate. Collectively, these findings expand our knowledge on helminth-induced immune modulation and support future investigations into the anti-inflammatory properties of TSPs for therapeutic purposes.